2021
DOI: 10.3389/fmicb.2021.630694
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gene Expression in Actinobacteria by Translational Modification of Transcriptional Factors and Secondary Metabolite Biosynthetic Enzymes

Abstract: Different types of post-translational modifications are present in bacteria that play essential roles in bacterial metabolism modulation. Nevertheless, limited information is available on these types of modifications in actinobacteria, particularly on their effects on secondary metabolite biosynthesis. Recently, phosphorylation, acetylation, or phosphopantetheneylation of transcriptional factors and key enzymes involved in secondary metabolite biosynthesis have been reported. There are two types of phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 130 publications
0
8
0
Order By: Relevance
“…After the BLAST alignment analysis of genes in clu13 (), six regulatory factors, four transport-related proteins, and a two-component system protein were investigated (Data S1), and they were likely to affect secondary metabolism. However, the transcriptional abundance of these genes in the clu13 cluster was low, which suggested that they were unlikely to affect the butenyl-spinosyn biosynthesis. However, a hypothetical protein, Sp1764, with high transcriptional abundance attracted our attention (Data S1; Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…After the BLAST alignment analysis of genes in clu13 (), six regulatory factors, four transport-related proteins, and a two-component system protein were investigated (Data S1), and they were likely to affect secondary metabolism. However, the transcriptional abundance of these genes in the clu13 cluster was low, which suggested that they were unlikely to affect the butenyl-spinosyn biosynthesis. However, a hypothetical protein, Sp1764, with high transcriptional abundance attracted our attention (Data S1; Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…In S. coelicolor , even though the ATP-Glk also lacks DNA-binding motifs, the enzyme specifically affects the expression of 43 genes by a mechanism that awaits to be defined (Romero-Rodríguez et al, 2016 ). Recently, the report of Glk crotonylation by an acyltransferase opened a plausible mechanism to explain how the modified ATP-Glk may interact with its corresponding transcriptional factors (Martín et al, 2021 ; Sun et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…SAM activates actinorhodin biosynthesis by increasing the autophosphorylation of AfsK ( Lee et al, 2007 ; Jin et al, 2011 ). Moreover, two other serine/threonine kinases, AfsL and PkaG, that can phosphorylate AfsR in vitro have been identified ( Sawai et al, 2004 ; Liu et al, 2013 ; Martín et al, 2021 ). This finding suggested that AfsR works as a signal integrator of signals that are sensed by multiple serine/threonine kinases ( Horinouchi, 2003 ).…”
Section: The Regulatory Function Of Sarps In Secondary Metabolismmentioning
confidence: 99%